Tree or three : An elementary pronunciation course - Baker, Ann (New York Cambridge University Press, 2006)
This revised edition of Tree or Three? retains its simplicity and straightforward syllabus. The emphasis on minimal pairs, which made the original edition so popular, makes pronunciation practice light-hearted and accessible. * Clear rubrics for exercises with answer key and improved navigation make the material even more user-friendly.
Keywords: Ngôn ngữ Anh